RAFT-Derived Polymethacrylates as a Superior Treatment for Recurrent Vulvovaginal Candidiasis by Targeting Biotic Biofilms and Persister Cells - Wu, Xueqing; Zhang, Sisi; Xu, Xinxin; Shen, Laien; Xu, Boyun; Qu, Wenzhen; Zhuang, Wenyi; Locock, Katherine; Deighton, Margaret; Qu, Yue (Frontiers in Microbiology, 2019)
BAbstract Background: Vulvovaginal candidiasis (VVC) is a common infection in need of more effective treatment. Formation of epithelium-associated Candida biofilms and the presence of persister cells are among the major contributing factors to the recurrence of this condition. We have previously developed RAFT-derived polymethacrylates that are effective in killing C. albicans biofilms in vitro. This study aimed to examine the clinical potential of polymethacrylates as antifungals for treatment of recurrent VVC (RVVC). Methods: A mouse model of VVC was used to establish vaginal epithelium-associated biofilms, using C. albicans isolates from VVC/RVVC patients. A comparison was made of the efficacies of polymethacrylates and conventional antifungals, clotrimazole and nystatin, in killing Candida in epithelium-associated biofilms in vivo. Ex vivo biofilms were used for Candida population profiling and to quantify persister cells in vaginal epithelia. The potency of polymethacrylates and conventional antifungals against persister cells, either as sole agents or in combination, was assessed. Results: Polymethacrylates showed negligible local toxicity, resistance to vaginal acidity, and outstanding in vivo activity against vaginal epithelium-associated C. albicans biofilms. In in vivo tests polymethacrylates outperformed the conventional antifungals, nystatin and clotrimazole at concentrations 50 times below the over-the-counter concentrations. Using polymethacrylates was associated with fewer persister cells, and better eradication of persister cells pre-selected by conventional antifungals. Conclusions: This study systematically assessed the clinical potential of RAFT-derived polymethacrylates as an effective treatment for VVC/RVVC in a mouse model. Polymethacrylates effectively killed vaginal epithelium-related C. albicans in vivo by specially targeting biotic biofilms and persister cells. Treatment presented negligible local toxicity.